PHONOLOGICAL, SYNTAX, SEMANTIC, AND MORPHEMIC ACQUISITION IN CHILDREN AGED 4-5 YEARS AT DAYCARE AND LEARNING GROUPS OF FARHANY KHAIR ISLAMIC SCHOOL - Dewi, Resti Citra; Anjas Wulan, Dwi Septi; Khairani, Alya; Zanna, Lita Rahma; Supriadi, Supriadi (Jurnal Buah Hati, 2025)
Language acquisition is a natural process that occurs since a child is born through interaction with the surrounding environment. Children aged 4-5 years are in a stage of rapid language development, where they begin to understand, pronounce, and use language in various communication situations. This study aims to analyze the acquisition of Indonesian in children aged 4-5 years at Daycare and Learning Groups of Farhany Khair Islamic School in terms of phonetics, semantics, syntax, and morphemics. The research method used is a qualitative method with a case study approach. Data collection techniques used through observation and recording of children's conversations in various interaction contexts. The results of the study on phonological analysis show that children aged 4-5 years are in the stage of phonological development, especially in the pronunciation of the consonant /r/. In syntactic analysis, children have not used the appropriate formal grammar rules, but the sentences spoken are communicative and show good language skill development. In semantic analysis, children have shown the ability to state conditions and solutions directly, can connect actions with their consequences, show an understanding of time and causal relationships, and begin to develop simple narrative flows. In the morphemic analysis, it shows that children begin to master the use of the passive prefix di- correctly; the morphological form is not standard, but its function as a passive verb is still understood. Children at this age tend to use free morphemes and are still in the process of acquiring affixation.